Population status of oribi (Ourebia ourebi Zimmermann, 1783) in Maze National Park, southern Ethiopia - Tekalign, Wondimagegnehu; Bekele, Afework (Bangladesh Journal of Zoology, 2015)
The population status of oribi (Ourebia ourebi Zimmermann, 1783) was carried out in the newly established Maze National Park, Ethiopia for two consecutive years (October 2009 to December 2011). A total count method was employed based on silent detection method in an area of 220 km2. A total of 894 and 1103 individuals were counted during the two consecutive years, respectively. Seasonal variation was significantly different with more individuals during the dry season than the wet season (p<0.05). The density of oribi over the whole area was 3.40 and 4.36 during the wet and 4.72 and 5.66 individuals per km2 during the dry seasons in both years, respectively. The study was important for future conservation measures as the oribi is the flagship species of the area. Bangladesh J. Zool. 41(2): 145-151, 2013